Communication in the Industrial Revolution Era 4.0 Through Learning Based Learning and Inquiry - Denny Denmar; Bradley Setiyadi; Sophia Rahmawati (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
Communication is known as an activity carried out verbally and non-verbally. Communication involves a large number of XXI century skills such as analysis, evaluation, problem solving, metacognition, collaboration, and technology. Some content standards that were built as a foundation for CCSS (Common Core State Standards) target communication skills in the ability to write, speak, and listen. Communication skills of jambi university education administration students seem to be lacking. This is reinforced by the results of observations, when discussion groups of students find it difficult to convey ideas verbally and difficulty in writing ideas into summaries. Lack of communication skills is influenced by many factors. While communication skills are very important possessed by students especially in the industrial era 4.0. One solution to improve communication skills is to integrate learning models. learning models that can be integrated are problem based learning and inquiry. The purpose of this study was to determine the improvement of communication skills of jambi university education administration students through the problem based learning model and the inquiry model. This research is a classroom action research (CAR) conducted in cycles of 4 stages, namely: planning, implementing, observing, and reflecting. The results of this CAR indicate that the inquiry model has not been able to show any indication of changes in improving communication skills of Educational Administration students in Jambi University